Reduction in Factor VII, Fibrinogen and Plasminogen Activator Inhibitor-1 Activity after Surgical Treatment of Morbid Obesity - Primrose, J N; Davies, J A; Prentice, C R M; Hughes, R; Johnston, D (Thrombosis and Haemostasis, 1992)
The aim of this study was to determine the effects of the surgical treatment of morbid obesity on some aspects of haemostatic and fibrinolytic function. Measurement of haemostatic and fibrinolytic factors was performed before and again 6 and 12 months after operation in 19 patients suffering from morbid obesity. Surgical treatment resulted in a mean decrease in body weight of 50 kg at 6 months and 64 kg at 12 months. Weight loss was accompanied at 12 months by significant reductions in median (interquartile range) concentrations of serum cholesterol from 5.3 (4.5–6.2) mmol/1 to 3.6 (2.9–4.6) mmol/1; factor VII from 113 (92–145)% of normal to 99 (85–107)%; of fibrinogen from 3.5 (3–9.3) g/1 to 2.8 (2.4–3.8) g/1; and of plasminogen activator inhibitor-1 (PAI-1) activity from 21 (11–30) IU/ml to 6.3 (5–10) IU/ml. The decrease in PAI-1 activity probably accounted for a significant reduction in euglobulin clot lysis time. Tissue plasminogen activator activity was undetectable in most patients pre-operatively but increased slightly after 1 year to 110 (100–204) mIU/ml. There were no significant changes in plasma levels of KCCT, factor VIII, von Willebrand factor antigen, alpha-2-antiplasmin, antithrombin III, protein C antigen, beta thromboglobulin, platelet factor 4, fibrinopeptide A or platelet count. These findings provide support for the hypothesis that the surgical treatment of morbid obesity may have a long-term beneficial effect on mortality from cardiovascular and thromboembolic disease.